Transfer Pricing Under Bilateral Bargaining. - Chalos, Peter; Haka, S. (The Accounting Review, 1990)
Abstract Examines negotiated transfer-pricing outcomes between a buying and selling division by using a bilateral bargaining methodology. Motivation and hypotheses; Manipulation checks and subject cavariates; Implications for research.